2009
DOI: 10.1063/1.3152743
|View full text |Cite
|
Sign up to set email alerts
|

Infrared spectra of the OCS-CO2 complex: Observation of two distinct slipped near-parallel isomers

Abstract: Infrared spectra of OCS-CO(2) complexes are studied in a pulsed supersonic slit-jet expansion using a tunable diode laser probe in the 2060 cm(-1) region of the C-O stretching fundamental of OCS. Two bands are observed and analyzed, corresponding to two distinct isomers of the complex. Isomer a is the known form which has been previously studied in the microwave region. Isomer b is a new form, expected theoretically but first observed here. Structures are determined with the help of isotopic substitution. Both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…The fact that we could observe the XeÁ Á ÁOCS complex is not particularly surprising, as many OCS complexes have been studied previously, including complexes of OCS with a single atom [3][4][5][6][7][8][9] or a di-/tri-atomic partner. [10][11][12] Initially, we thought that somebody must have studied this complex before, as it is the last one in series of OCS complexes with non-radioactive noble gases. However, it does not seem to be the case, and it is up to us to fill this particular gap in this series of homologues.…”
Section: Introductionmentioning
confidence: 99%
“…The fact that we could observe the XeÁ Á ÁOCS complex is not particularly surprising, as many OCS complexes have been studied previously, including complexes of OCS with a single atom [3][4][5][6][7][8][9] or a di-/tri-atomic partner. [10][11][12] Initially, we thought that somebody must have studied this complex before, as it is the last one in series of OCS complexes with non-radioactive noble gases. However, it does not seem to be the case, and it is up to us to fill this particular gap in this series of homologues.…”
Section: Introductionmentioning
confidence: 99%
“…1 It has been reported that one molecule of N 2 O has approximately 300 times the greenhouse warming potential of one molecule of CO 2 . The van der Waals (vdW) complexes of these "CO 2 family" molecules, especially their dimers [4][5][6][7][8][9][10][11][12][13][14][15][16][17] and trimers, [18][19][20] have been the focus of both experiment and theory over the past few years. 2,3 Therefore, the N 2 O molecule and N 2 O-including complexes are of particular interest in the field of atmospheric chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…The fact that we could observe the Xe• • •OCS complex is not particularly surprising, as many OCS complexes have been studied previously, including complexes of OCS with a single atom [3][4][5][6][7][8][9] or a di-/tri-atomic partner. [10][11][12] Initially, we thought that somebody must have studied this complex before, as it is the last one in series of OCS complexes with non-radioactive noble gases. However, it does not seem to be the case, and it is up to us to fill this particular gap in this series of homologues.…”
Section: Introductionmentioning
confidence: 99%